2016
DOI: 10.3168/jds.2015-9589
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Staphylococcus aureus: Subtyping, evolution, and zoonotic transfer

Abstract: Staphylococcus aureus is globally one of the most important pathogens causing contagious mastitis in cattle. Previous studies using ribosomal spacer (RS)-PCR, however, demonstrated in Swiss cows that Staph. aureus isolated from bovine intramammary infections are genetically heterogeneous, with Staph. aureus genotype B (GTB) and GTC being the most prominent genotypes. Furthermore, Staph. aureus GTB was found to be contagious, whereas Staph. aureus GTC and all the remaining genotypes were involved in individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
97
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 54 publications
13
97
1
3
Order By: Relevance
“…aureus genotypes (GTOG) were rarely present (Fournier et al, 2008). Studies by and Boss et al (2016) confirmed the Swiss results at the European level: Staph. aureus GTB, GTC, and GTR were the most prominent genotypes, followed by GTF, GTI, and a set of 41 genotypes with rare occurrence.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…aureus genotypes (GTOG) were rarely present (Fournier et al, 2008). Studies by and Boss et al (2016) confirmed the Swiss results at the European level: Staph. aureus GTB, GTC, and GTR were the most prominent genotypes, followed by GTF, GTI, and a set of 41 genotypes with rare occurrence.…”
Section: Introductionsupporting
confidence: 58%
“…Analysis of the spa type was performed as described by Boss et al (2016). In brief, the variable X region of the spa gene was amplified in a total volume of 25 μL containing 300 nmol of each spa primer , 12.5 μL of HotStarTaq master Mix (Qiagen), and 2.5 μL of DNA diluted 1:20 in H 2 O.…”
Section: Spa Typingmentioning
confidence: 99%
See 1 more Smart Citation
“…One was related to the equipment used. The use of a miniaturized electrophoresis system (Agilent Technologies) has been recommended for best resolution, data evaluation, and data management of RS-PCR results (34). The suggested system can be expensive, and it is not necessarily available in all laboratories conducting PCR, which may be considered a limitation pertaining to this technique.…”
Section: Discussionmentioning
confidence: 99%
“…This study and previous data [5, 6] confirmed that particular gene patterns, virulence profiles and specific genotypes could be associated with diverse clinical outcomes. More recently, two large European studies [7, 8], demonstrated that the Repetitive-Sequence PCR RS-PCR genotype B (GTB), belonging to the Sequence Type ST8 [9, 10], a high contagious and diffusive Staph. aureus involved in bovine IMI, was the most frequently detected in several European countries (Austria, Belgium, France, Germany, Italy, Switzerland).…”
Section: Introductionmentioning
confidence: 99%